Catalytic access to ferrocenyl phosphines bearing both planar and central chirality – A kinetic resolution approach via catalytic asymmetric P(III)–C bond formation. Issue 25 (19th June 2020) - Sadeer, Abdul; Kojima, Tadayuki; Ng, Jia Sheng; Gan, Kennard; Chew, Renta Jonathan; Li, Yongxin; Pullarkat, Sumod A.
Abstract: A series of enantioenriched ferrocenyl monophosphines imbued with both central and planar chirality were obtained catalytically (80–99% ee ) via the kinetic resolution of 1, 2-disubstituted planar chiral ferrocenyl enone racemates. The synthetic approach utilized a chiral palladacycle to facilitate the asymmetric hydrophosphination (AHP) as a means to achieve high stereoselectivity. The enantioenriched ferrocenylphosphine products could be protected and further recrystallized to obtain ee s up to 99%. The modularity of the phosphine framework obtained was demonstrated via derivatization of its functional handles via a simple nucleophilic substitution to yield optically pure bisphosphines. Graphical abstract: Image 1 Highlights: Route towards ferrocenyl phosphines bearing both central and planar stereogenic elements. Employs catalytic asymmetric P–H addition protocol to achieve efficient kinetic resolution. Allows generation of 1, 2 diphosphines from racemic substrates.